Do Sustainability Reports Make Sense for Asset Selection? - Lachuer, Julien; Lilti, Jean-Jacques (Management international / International Management / Gestiòn Internacional, 2021)
The purpose of this article is to determine whether the discourse in sustainability reports and in the CEOs’ opening speech is likely to provide relevant information to asset managers. Our results show that greenwashing and entrenchment strategies from executives are detrimental to the social and financial performance of portfolios. Thus, our study combines lexical analysis with data on financial performance and level of responsibility. The methodology developed enables us to reveal what is not said and to establish a reading grid that limits the risk of informational asymmetry.